Aplikasi Fuzzy MADM (Multi Attribute Decision Making) Metode Topsis Untuk Identifikasi Servqual - Binti Karomah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
One Fuzzy method used for decision making is fuzzy multi attribute decision making, or fuzzy MADM, which can be applied in economics, particularrybin assesing and identifying costumer satisfaction. In this study the TOPSIS method is based on the concept that the best selected alternative not only has the shortest distance from the positive ideal solution but also has the longest distance from the negative ideal solution. The positive ideal solution (A+) and the negative ideal solution (A-) can be determined based on the normalized weight rating (Yij). Based on this study, the final result show that the service quality currently provided by shopping centers is unsatisfactory.All seven criteria require improvement, including general conditions, atmosphere, price, merchandise, service, facilities and guarantees. Four criteria must be optimized atmosphere, merchandise, facilities, and guarantees.